Genomic signatures of population bottleneck and recovery in Northwest Atlantic pinnipeds. Issue 13 (5th June 2018) - Cammen, Kristina M.; Schultz, Thomas F.; Don Bowen, W.; Hammill, Michael O.; Puryear, Wendy B.; Runstadler, Jonathan; Wenzel, Frederick W.; Wood, Stephanie A.; Kinnison, Michael
Abstract: Population increases over the past several decades provide natural settings in which to study the evolutionary processes that occur during bottleneck, growth, and spatial expansion. We used parallel natural experiments of historical decline and subsequent recovery in two sympatric pinniped species in the Northwest Atlantic, the gray seal ( Halichoerus grypus atlantica ) and harbor seal ( Phoca vitulina vitulina ), to study the impact of recent demographic change in genomic diversity. Using restriction site‐associated DNA sequencing, we assessed genomic diversity at over 8, 700 polymorphic gray seal loci and 3, 700 polymorphic harbor seal loci in samples from multiple cohorts collected throughout recovery over the past half‐century. Despite significant differences in the degree of genetic diversity assessed in the two species, we found signatures of historical bottlenecks in the contemporary genomes of both gray and harbor seals. We evaluated temporal trends in diversity across cohorts, as well as compared samples from sites at both the center and edge of a recent gray seal range expansion, but found no significant change in genomewide diversity following recovery. We did, however, find that the variance and degree of allele frequency change measured over the past several decades were significantly different from neutral expectations of drift under population growth. These two cases of well‐described demographic history provide opportunities for critical evaluation of current approaches to simulating and understanding the genetic effects of historical demographic change in natural populations. Abstract : In parallel natural experiments of historical decline and subsequent recovery in two sympatric pinniped species in the Northwest Atlantic, the gray seal ( Halichoerus grypus atlantica ) and harbor seal ( Phoca vitulina vitulina ), we used restriction site‐associated DNA sequencing to study the impact of recent demographic change on genomic diversity. Despite significant differences in the degree of genetic diversity assessed in the two species, we found signatures of historical bottlenecks in the contemporary genomes of both gray and harbor seals. We evaluated temporal trends in diversity within cohorts, as well as compared samples from sites at both the center and edge of a recent gray seal range expansion, but found no significant change in genomewide diversity following recovery.